At risk of being risky: The relationship between "brain age" under emotional states and risk preference. (April 2017) - Rudolph, Marc D.; Miranda-Domínguez, Oscar; Cohen, Alexandra O.; Breiner, Kaitlyn; Steinberg, Laurence; Bonnie, Richard J.; Scott, Elizabeth S.; Taylor-Thompson, Kim; Chein, Jason; Fettich, Karla C.; Richeson, Jennifer A.; Dellarco, Danielle V.; et al.
Highlights: Multivariate-analyses significantly predict age in randomized train & test groups using pseudo-resting state data. Emotional states affect underlying functional connectivity and lead to changes in an individual's predicted "brain age". Under emotional states adolescents on average demonstrated a reduction in "brain age" from their true age (i.e., a younger brain phenotype). On average, a phenotype of a younger "brain age" during emotional states, relative to a neutral state is related to risk preference and perception. Abstract: Developmental differences regarding decision making are often reported in the absence of emotional stimuli and without context, failing to explain why some individuals are more likely to have a greater inclination toward risk. The current study (N = 212; 10–25y) examined the influence of emotional context on underlying functional brain connectivity over development and its impact on risk preference. Using functional imaging data in a neutral brain-state we first identify the "brain age" of a given individual then validate it with an independent measure of cortical thickness. We then show, on average, that "brain age" across the group during the teen years has the propensity to look younger in emotional contexts. Further, we show this phenotype (i.e. a younger brain age in emotional contexts) relates to a group mean difference in risk perception − a pattern exemplified greatest in young-adults (ages 18–21). The results are suggestive of a specified functional brain phenotype that relates to being at "risk to be risky."